Autonomy, Independence, Inclusion - Filippo Angelucci; Cristiana Cellucci; Michele Di Sivo; Daniela Ladiana (Techne, 2015)
The living environment must not only meet the primary needs of living, but also the expectations of improvement of life and social relations and people’s work. The need for a living environment that responds to the needs of users with their different abilities, outside of standardizations, is increasingly felt as autonomy, independence and well-being are the result of real usability and adaptability of the spaces. The project to improve the inclusivity of living space and to promote the rehabilitation of fragile users need to be characterized as an interdisciplinary process in which the integration of specialized contributions leads to adaptive customization of space solutions and technological that evolve with the changing needs, functional capacities and abilities of individuals.